Assessing climate change impact on storm surge and funding strategies in east peninsular Malaysia - Rosli, Nurdiyana Nabilah; Teh, Hee-Min; Kim, Sooyoul (Frontiers in Climate, 2025)
Climate change is intensifying storm surge risks in Southeast Asia, particularly along Malaysia’s east coast facing the South China Sea. This study uses the d4PDF climate dataset to simulate maximum storm surge heights under 2 °C and 4 °C global warming scenarios. Results show that projected surge heights exceed 1 meter at all key coastal stations, with localized surges reaching up to 1.8 meters. By integrating these projections with 2014–2024 flood loss statistics and national budget allocations, the study identifies a concerning mismatch between increasing storm surge risks and current mitigation investments, suggesting that existing policy frameworks are underfunded and may lack the capacity to adequately protect high-risk coastal areas. To address this, the study recommends the development of a unified regional storm surge prediction and response system that integrates real-time data and supports cross-border coordination. It also proposes the establishment of standardized infrastructure guidelines tailored to storm surge resilience, and calls for increased investment in community-based risk mapping powered by artificial intelligence (AI). These strategies provide an actionable framework for strengthening disaster management, improving policy responsiveness, and enhancing coastal resilience across Malaysia and Southeast Asia.